OʻQUVChILARNING MULOQOT MADANIYATINI AKSIOLOGIK YONDAShUVLAR ASOSIDA ShAKLLANTIRISh ILMIY-METODIK MUAMMO SIFATIDA - Ibodullayeva, I. (SCIENCE and SOCIETY, 2025)
This article discusses how communication culture, establishing effective communication, or engaging in communication are becoming integral criteria of society. The organization of a quality educational environment through the effective use of advanced educational systems of leading countries, innovative and integrative achievements in the field of education, pedagogical methods, and skills of global experts has become one of the priority strategic goals of the educational systems of developing countries. The article also emphasizes the importance of forming communication culture in students based on axiological approaches.